2001
DOI: 10.1080/15216540152845920
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Complex I: Progress in Understanding of Catalytic Properties

Abstract: SummaryAlthough the mitochondrial Complex I has been extensively studied for over 4 decades, its catalytic properties in mitochondria are poorly understood. This review summarizes the data on standard and nonstandard kinetic parameters of the enzyme. The slow interconversion between active and deactivated forms of the mammalian Complex I (A/D transition) is described. We discuss the potential relevance of this transition for the regulation of NADH oxidation by the respiratory chain under physiological and path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 39 publications
1
47
2
Order By: Relevance
“…It was suggested that progressive impairment of several components of the mitochondrial function measured in permeabilised heart muscle fibres, such as oxidative phosphorylation (OXPHOS, respiratory state III), ATP production efficiency and the capacity of single complexes of the Electron Transport System (ETS) shape the temperature of heart failure (T HF ). High temperature changes the fluidity of mitochondrial membranes, which can entail increased proton leak through the inner membrane ([19] for review), resulting in decreased coupling ratios and causing decreased membrane potential [34, 35] and, as a consequence, inhibit the electrogenic transport of substrates, i. e. the transport of charged substrates like glutamate and malate that leads to the translocation of net charge across the membrane [36]. This indicates that mitochondrial metabolism is involved in functional constraints and thermal limitation of this tissue [28, 29, 32, 33].…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that progressive impairment of several components of the mitochondrial function measured in permeabilised heart muscle fibres, such as oxidative phosphorylation (OXPHOS, respiratory state III), ATP production efficiency and the capacity of single complexes of the Electron Transport System (ETS) shape the temperature of heart failure (T HF ). High temperature changes the fluidity of mitochondrial membranes, which can entail increased proton leak through the inner membrane ([19] for review), resulting in decreased coupling ratios and causing decreased membrane potential [34, 35] and, as a consequence, inhibit the electrogenic transport of substrates, i. e. the transport of charged substrates like glutamate and malate that leads to the translocation of net charge across the membrane [36]. This indicates that mitochondrial metabolism is involved in functional constraints and thermal limitation of this tissue [28, 29, 32, 33].…”
Section: Introductionmentioning
confidence: 99%
“…Despite advanced biochemical analysis of the kinetic behavior of both forms of complex I (20), the functional role of the observed heterogeneity has not yet been explained. We have now investigated the effect of nitrosothiols and ONOO Ϫ on the A-and D-forms of the enzyme.…”
mentioning
confidence: 99%
“…Two catalytically and structurally distinct forms exist in any given preparation of the enzyme as follows: one is the fully competent, so-called "active" A-form and the other is the disabled, silent, "de-activated" D-form. Socalled pseudoreversible A/D transitions have been described in mammalian complex I (18) and other eukaryotic complex I (19) and have been reviewed in detail (17,20). After exposure of idle enzyme preparations (mitochondria (21), submitochondrial particles (SMP) (18), or purified complex I (22)) to elevated but physiological temperatures (Ͼ30°C) in the absence of substrate, when catalytic turnover cannot occur, the enzyme converts to the D-form.…”
mentioning
confidence: 99%
“…Maintenance of the fraction of complex I in the D-form would allow fast responses to changes in conditions such as a reductive pressure, ATP demand and oxygen availability by analogy with the well-known phenomenon of excess capacity of cytochrome c oxidase [44–46]. Therefore the A/D transition could be one of the mechanisms for fine-tuning enzyme activity in different tissues [5,18,47,48]. The time course of complex I deactivation after cardiac arrest reveals a much higher A/D transition rate in brain compared with heart tissue (Figure 2) and might explain the greater vulnerability of complex brain functions to oxygen deprivation.…”
Section: Physiological Effect Of the A/d Transitionmentioning
confidence: 99%